Rekonstruksi Folklor Batak Toba dalam Bentuk Pertunjukan Tortor Sigale-Gale - Rini H. Sinaga (Universitas Negeri Medan, 2016)
This study aims to determine how the existence of folklore in BatakToba society and pinpoint how